Updates in the management of unknown primary of the head and neck - Kalavacherla, Sandhya; Sanghvi, Parag; Lin, Grace Y.; Guo, Theresa (Frontiers in Oncology, 2022)
Squamous cell carcinoma (SCC) from an unknown primary tumor (SCCUP) accounts for 2.0%–5.0% of all head and neck cancers. SCCUP presents as enlarged cervical lymph nodes without evidence of a primary tumor upon physical examination. Primary site detection is important to target treatment and avoid treatment-related morbidity. In this review, we discuss updates in SCCUP management. Diagnostic workup should focus on localization of the primary tumor in SCCUP. Initial workup centers on neck biopsy to confirm the presence of SCC. Given the increasing incidence of HPV-related SCC in the oropharynx, HPV testing is crucial. An HPV-positive status can localize the tumor to the oropharynx, a common site for occult tumors. Imaging includes neck CT and/or MRI, and PET/CT. After imaging, panendoscopy, palatine tonsillectomy or diagnostic transoral robotic surgery can facilitate high rates of primary tumor localization. Primary tumor localization influences treatments administered. SCCUP has traditionally been treated aggressively with large treatment fields to all potential disease sites, which can induce weight loss and swallowing dysfunction. As a result, primary localization can reduce radiation fields and provide possible de-escalation to primary surgical management. Advances in intensity-modulated radiation therapy and dose management also have the potential to improve functional outcomes in SCCUP patients. Given the improved prognosis associated with HPV-positive SCCs, HPV tumor status may also inform future treatment de-intensification to reduce treatment-related toxicity.